2017
DOI: 10.1007/s10006-017-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D plate and locking plate in treatment of mandibular fracture—a clinical study

Abstract: Both 3D titanium miniplates and locking plate are effective in the treatment of mandibular fractures, and overall complication rates are lesser. However, the 3D plating system uses less hardware in cases of parasymphysis and symphysis fractures and more hardware in cases of body and angle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…For intra-articular fracture of the thumb, the fixing pin was inserted on the side central line at the radial thumb. For intra-articular fracture of the index finger, middle finger, and ring finger, the fixing pin should be inserted at a 45 °angle from the dorsoradial branch to the horizontal plane; also, it could be inserted at a 45 °angle from the dorsoulnar branch to the horizontal plane for intraarticular fracture of the middle finger and ring finger [12][13][14]. For intra-articular comminuted fracture of the little finger, the fixing pin was inserted on the side central line of the ulnar branch of the little finger.…”
Section: Methodsmentioning
confidence: 99%
“…For intra-articular fracture of the thumb, the fixing pin was inserted on the side central line at the radial thumb. For intra-articular fracture of the index finger, middle finger, and ring finger, the fixing pin should be inserted at a 45 °angle from the dorsoradial branch to the horizontal plane; also, it could be inserted at a 45 °angle from the dorsoulnar branch to the horizontal plane for intraarticular fracture of the middle finger and ring finger [12][13][14]. For intra-articular comminuted fracture of the little finger, the fixing pin was inserted on the side central line of the ulnar branch of the little finger.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the evaluation of quality, 8 studies 9,15-21 showed a low value of the risk of bias, 17 a moderate risk 2,6,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and 19 a high risk 1,5,8,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (Supplementary Digital Content, Table 1, http:// links.lww.com/SCS/C680).…”
Section: Analysis Of Sensitivity and Publication Biasmentioning
confidence: 99%
“…Conflict of interest was not reported in 12 studies 12,[25][26][27]32,33,37,39,41,42,46 . In 18 studies informed consent was reported 11,13,22,23,27,29,31,[35][36][37][38][43][44][45][48][49][50][51] .…”
Section: Characteristics and Quality Of Included Primary Studiesmentioning
confidence: 99%
“…In total, 16 studies were selected for the meta-analysis. Reasons for not being included in the meta-analysis were: comparison of different diameter plates n = 5 38,39,41,44,45 (e.g., 2.0-mm locking vs. 2.3-mm non-locking), comparison of different plate designs n = 8 35,37,40,42,43,48,50,51 (i.e. 3D vs. 2.0 mm), comparison of single and double plates n = 2 36,47 , identical study n = 1 23 and duplicated study n = 1 24 .…”
Section: Meta-analysismentioning
confidence: 99%